Implementation of a PCR-based strategy to control an outbreak by Serratia marcescens in a Neonatal Intensive Care Unit - Ángel Rodríguez-Villodres; José Manuel Ortiz de la Rosa; Raquel Valencia-Martin; Francisco Jiménez Parrilla; Guillermo Martín-Gutiérrez; Natividad Márquez Patiño; Estela Perea Cruz; María Teresa Sánchez Jiménez; Antonio Pavón Delgado; José Miguel Cisneros; José Antonio Lepe (BMC, 2023)
Abstract Objectives To evaluate the clinical and epidemiological impact of a new molecular surveillance strategy based on qPCR to control an outbreak by Serratia marcescens in a Neonatal Intensive Care Unit (NICU). Methods We design a specific qPCR for the detection of S. marcescens in rectal swabs of patients admitted to a NICU. We divided the surveillance study into two periods: (a) the pre-PCR, from the outbreak declaration to the qPCR introduction, and (b) the PCR period, from the introduction of the qPCR until the outbreak was solved. In all cases, S. marcescens isolates were recovered and their clonal relationship was analysed by PFGE. Control measures were implemented during the outbreak. Finally, the number of bloodstream infections (BSI) was investigated in order to evaluate the clinical impact of this molecular strategy. Results Nineteen patients colonized/infected by S. marcescens were detected in the pre-PCR period (October 2020-April 2021). On the contrary, after the PCR implementation, 16 new patients were detected. The PFGE revealed 24 different pulsotypes belonging to 7 different clonal groups, that were not overlapping at the same time. Regarding the clinical impact, 18 months after the qPCR implementation, no more outbreaks by S. marcescens have been declared in the NICU of our hospital, and only 1 episode of BSI has occurred, compared with 11 BSI episodes declared previously to the outbreak control. Conclusions The implementation of this qPCR strategy has proved to be a useful tool to control the nosocomial spread of S. marcescens in the NICU.